WORK–LIFE BALANCE DIMENSIONS AS PREDICTORS OF WORK STRESS IN HOSPITAL NURSES: A CROSS-SECTIONAL STUDY - Puspitasari, Sagita Candra (Jurnal Penelitian, 2025)
Background: The nursing profession has high physical and mental demands that can interfere with nurses' ability to maintain work-life balance (WLB), thus potentially increasing work stress. This study aims to analyze the relationship between WLB determinants and work stress levels in inpatient nurses at Prof. Dr. Soekandar Mojosari Regional General Hospital. Method: The study design used a cross-sectional approach with 84 respondents selected through purposive sampling. Instruments included the WIPL, PLIW, PLEW, and WEPL questionnaires, and work stress questionnaires. The analysis used the Spearman correlation test. Results: WIPL had a significant negative relationship with work stress (p = 0.000; r = –0.499), and PLIW also showed a significant negative relationship (p = 0.021; r = –0.235). WEPL had a strong and significant negative correlation (p = 0.000; r = –0.557), indicating that the more work supports personal life, the lower the nurses' stress levels. However, PLEW did not show a significant relationship (p = 0.246; r = –0.117). This condition indicates that personal life support, such as family comfort or social environment, is not enough to offset the high work pressure, so it does not have a direct impact on stress reduction. Conclusion: This study confirms that the imbalance between work demands and personal life is an important factor affecting work stress. Hospitals need to strengthen strategies to improve WLB through flexible scheduling, adequate rest time, and psychological support to reduce nurses' work stress.